A Literature Review on Arnold-Chiari Disease in Children (Evaluation of Surgical Approach and Post-Surgical Management) - Michael; Rully Hanafi Dahlan; Sevline Estethia Ompusunggu (Talenta Publisher, 2025)
Background: Arnold-Chiari (AC) disease in children is a complex congenital condition requiring multidisciplinary management. Surgical intervention is often necessary to correct affected anatomy and alleviate symptoms. Objective: To investigate surgical approaches and post-surgical management of AC in children and identify knowledge gaps. Methods: Literature search was systematically conducted through PubMed using relevant keywords. Inclusion criteria encompassed studies within the past 15 years pertaining to pediatric neurosurgery and Chiari. Results: Six relevant studies highlighted the importance of intraoperative electrophysiological monitoring, comparison of outcomes between posterior decompression with and without duraplasty, correlation of CSF flow with surgical outcomes, post-operative pain management, and indications for syringosubarachnoid shunt placement. Knowledge gaps remain regarding long-term effects of monitoring techniques, surgical outcome comparisons, CSF flow relationships, and pain management. Conclusion: Surgical intervention for AC in children is critical, yet meticulous post-surgical management is required. Cross-disciplinary collaboration and a holistic approach are necessary to enhance understanding and care of AC in children.